Silence is golden? Silences as strategic narratives in Central Asian states' response to the Ukrainian crisis. (January 2023) - Dadabaev, Timur; Sonoda, Shigeto
Abstract: In this article, we argue that Central Asian (CA) states' approach to the Ukrainian crisis should be defined as strategic silence. Such foreign policy reflects how CA's ideological and geographic factors and a shared information space, largely dominated by Russian and Russian-language media, facilitate the understanding of historical continuity among Russian and CA leaders. However, we also demonstrate that CA public officials' and general public's uses of strategic silence reflect the complicated reality of CA states. Their leaders and populations are cognizant of both their dependence on educational and labor opportunities in Russia and their necessity for postwar coexistence with Russia, China, and other states that are not sympathetic to the intentions of the European Union/USA in CA. Therefore, strategic silence is an approach for CA states to voice their disagreement with Russia's approach to Ukraine while avoiding being victimized by Russia and its allies for an openly anti-war stance.